Different practices of selected private school libraries in terms of the selection and use of media collection in their school curricula - Arevalo, Jamaica R.; Golfo, Mary Grace P. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2012)
Since media have played a significant role on children's learning development and school libraries have an integral part in providing access to information through different media and meeting the needs of the school curricula, an analysis of the different practices of selected school libraries in terms of selection and use of media collection was made. This study generally aimed to determine the roles of the selected school libraries in advocating a student centered learning. These selected school libraries were Assumption College of Makati, Ateneo de Manila University, Claret School of QC, Colegio San Agustin of Makati and St. Scholastica's of Marikina. This paper also looked into the collection development practices of the schools, especially in the selection and utilization of media materials as curriculum support and the existing collaboration between the Library Media Specialist (LMS) and teachers and/or subject coordinators.
From the five schools selected, only three schools responded namely the Assumption College of Makati, Claret School of QC and Colegio San Agustin of Makati. Among the schools, survey questionnaires were given to the LMS and 10% sample from the grade school teachers and/or subject coordinators. Based from the results of the survey, Assumption College of Makati obtained the highest number of titles and quantity of print, non-print media and equipment. It is followed by Colegio San Agustin of Makati and then Claret School of QC (see Tables 3 to 7). The advantage of Assumption College of Makati to other school is the library budget of more than Php 3,000,000. Furthermore, in terms of the collection development practices, especially, selection, most of the members of the school community such as administrators, subject specialist, LMS, teachers and students participate to provide their needs in classroom instruction and research. In the utilization of media, the three schools require a valid ID in borrowing materials. Non print and equipment are only allowed for class use and requires a request form filled by the teacher assigned. According to the outcome, the three schools mostly use print media such as textbooks in the five major subjects; non print media namely flowcharts, diagrams, models, and posters in Science, and globes and maps in Social Studies; equipment such as computers, laptops, LCD projectors, transparencies, overhead projectors and televisions. In collaboration, the three schools agreed that during school activities LMS and teachers/and or subject coordinators "always" collaborate and actively participate (except from Claret School of QC which rated as "often") in activities such as classroom instruction, acquisition, selection and evaluation of media collection. Moreover, the selected schools showed that they have "excellent" media collection in terms of currency and quantity except from Claret School of QC which rated their collection as "adequate".
Recommendations included having more acquisitions of print, non-print and especially equipment to suffice all subject areas being taught, having library orientations for teachers to familiarize their collection and strengthening their committee of teachers to meet the needs of their users and school curricula.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: School libraries -- (Collection development).; Instructional materials -- Collection development -- Philippines -- Manila Metropolitan Area